2010
DOI: 10.1007/s11552-010-9308-2
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Sleep Position on the Side is Associated with Carpal Tunnel Syndrome

Abstract: Our findings of a strong association between the presence of carpal tunnel syndrome and preferred sleeping on the side suggest a comprehensive unifying theory of causation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 33 publications
2
32
0
1
Order By: Relevance
“…In our study, 59.7% of the patients slept on their right sides. This finding was consistent with a study in America [16]. Recent studies showed sleep positions affect quality of life [21].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In our study, 59.7% of the patients slept on their right sides. This finding was consistent with a study in America [16]. Recent studies showed sleep positions affect quality of life [21].…”
Section: Discussionsupporting
confidence: 93%
“…In this case-control study, a significant relationship was found between sleeping on either sides and the prevalence of CTS. Moreover, the findings of this study showed this relationship is stronger in men compared to the women [16].…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations